Body mass prediction from skeletal frame size in elite athletes - Ruff, C. B. (American Journal of Physical Anthropology, 2000)
Body mass can be estimated from measures of skeletal frame size (stature and bi-iliac (maximum pelvic) breadth) fairly accurately in modern human populations. However, it is not clear whether such a technique will lead to systematic biases in body mass estimation when applied to earlier hominins. Here the stature/bi-iliac method is tested, using data available for modern Olympic and Olympic-caliber athletes, with the rationale that these individuals may be more representative of the general physique and degree of physical conditioning characteristic of earlier populations. The average percent prediction error of body mass among both male and female athletes is less than 3%, with males slightly underestimated and females slightly overestimated. Among males, the ratio of shoulder to hip (biacromial/bi-iliac) breadth is correlated with prediction error, while lower limb/trunk length has only a weak inconsistent effect. In both sexes, athletes in "weight" events (e.g. , shot put, weight-lifting), which emphasize strength, are underestimated, while those in more endurance-related events (e.g., long distance running) are overestimated. It is likely that the environmental pressures facing earlier hominins would have favored more generalized physiques adapted for a combination of strength, speed, agility, and endurance. The events most closely approximating these requirements in Olympic athletes are the decathlon, pentathlon, and wrestling, all of which have average percent prediction errors of body mass of 5% or less. Thus, "morphometric" estimation of body mass from skeletal frame size appears to work reasonably well in both "normal" and highly athletic modern humans, increasing confidence that the technique will also be applicable to earlier hominins.